1997
DOI: 10.1021/ac960846e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior and Determination of the Insecticide Synergist Piperonyl Butoxide

Abstract: Piperonyl butoxide may be reversibly oxidized in acetonitrile at a glassy carbon electrode to a cation radical under short time scale voltammetric conditions, e.g., cyclic voltammetry when the potential scan rate is above 500 mV s(-)(1). During longer time domain experiments, the cation radical decays in a rate-limiting heterolytic bond cleavage step and subsequent transfer of a second electron at the potential of the first process. Additionally, a second oxidation process develops at more positive potentials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…At pH 7 and 8, a second poorly resolved wave is seen at E p = +1.40 V. Considering the molecular structure, it is reasonable to assume that the main oxidation peak observed could only be ascribed to the unique function present in the molecule susceptible to be oxidized, the oxygen aromatic ether. Previous work on similar alkoxybenzenes and literature data indicated that the oxidation process proceeds at the aromatic nucleus, through a one-electron transfer, via the formation of an unstable cation-radical intermediate that could undergo further subsequent reactions. The second poorly resolved wave observed at pH 7 and 8, not detected for fluoxetine, must then be related to the oxidation of the species resulting from the formation and dimerization of the initial cation radical (Scheme ). , As this moiety is present in fluoxetine (Scheme ), it seems reasonable to infer that the pharmaceutical drug shares the same oxidation pattern. Moreover, the results observed for this analogue, and in particular the evidence of the formation of dimeric species, could contribute to explain the strong adsorption processes that occur when using glassy carbon electrodes for measuring fluoxetine, which is perhaps the main reason for the limited use of electrochemical methods for its quantification. , …”
Section: Resultsmentioning
confidence: 94%
“…At pH 7 and 8, a second poorly resolved wave is seen at E p = +1.40 V. Considering the molecular structure, it is reasonable to assume that the main oxidation peak observed could only be ascribed to the unique function present in the molecule susceptible to be oxidized, the oxygen aromatic ether. Previous work on similar alkoxybenzenes and literature data indicated that the oxidation process proceeds at the aromatic nucleus, through a one-electron transfer, via the formation of an unstable cation-radical intermediate that could undergo further subsequent reactions. The second poorly resolved wave observed at pH 7 and 8, not detected for fluoxetine, must then be related to the oxidation of the species resulting from the formation and dimerization of the initial cation radical (Scheme ). , As this moiety is present in fluoxetine (Scheme ), it seems reasonable to infer that the pharmaceutical drug shares the same oxidation pattern. Moreover, the results observed for this analogue, and in particular the evidence of the formation of dimeric species, could contribute to explain the strong adsorption processes that occur when using glassy carbon electrodes for measuring fluoxetine, which is perhaps the main reason for the limited use of electrochemical methods for its quantification. , …”
Section: Resultsmentioning
confidence: 94%
“…Table 1 shows a short review of electroanalytical procedures developed for the determination of pesticides on glassy carbon electrodes [19,[21][22][23][24][25][26][27][28][29][30][31][32]. As it can be seen, most of the determinations were based on the oxidation of the parent product on the electrode surface, whereas some carbamate insecticides could only be determined by electroanalytical methods after their alkaline hydrolysis to a phenolic product, which can be easily oxidised on the glassy carbon electrode.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of o-quinone moiety in the sanguinarine and chelerythrine molecule can occur via oxidation of methylenedioxysubstituted benzene ring. Oxidations of various 1,3-benzodioxole derivatives (methylenedioxyamphetamines [15], derivative of piperonal [16] and 1,3-benzodioxole itself [17]) generally proceed at potentials above 800 mV vs. SCE in aqueous solutions. The formation of "a species, which is reversibly oxidized at less positive potentials" is reported to occur during oxidation of 1,3-benzodioxole in fluorosulfonic acid at À 78 8C [17].…”
mentioning
confidence: 99%